The isolation and characterization of Rhizobium loti exopolysaccharide mutants : a thesis presented in partial fulfilment of the requirements for the Degree of Doctor of Philosophy in Molecular Genetics at Massey University, Palmerston North, New Zealand - Hotter, Grant Spencer (Massey University, 1991)
PN1 84, a streptomycin resistant derivative of the broad host range Rhizobium loti strain NZP2037, was shown to be Calcofluor-bright due to the production of a Calcofluor-binding exopolysaccharide (EPS) with both high and low molecular weight forms, the low molecular weight form being predominant Eight Calcofluor-dark EPS mutants (three smooth and five rough) were generated by Tn5 mutagenesis of PN1 84. Each mutant was shown to carry a single , independent Tn5 insertion. Cosmids that complemented the mutation carried by each of the rough, PN1 84-derived EPS mutants were isolated from a pLAFRl gene library to NZP2037 by complementation of the Calcofluor-dark phenotype. The genetic regions identified were shown to be located on the chromosome, and were not closely linked. The mutants were divided into three (complementation) groups. While the rough, PN1 84-derived EPS mutants failed to synthesize EPS, the smooth, PN1 84-derived EPS mutants were found to synthesize an EPS which failed to bind Calcofluor, and which was shown, by 1 H-NMR spectroscopy, to be significantly less acetylated than the EPS produced by PN1 84. Furthermore, PN1 177, one of the smooth, PN1 84-derived EPS mutants, was shown to produce only a small amount of high molecular weight EPS compared to PN1 84. All the PN1 84-derived EPS mutants induced the formation of fully effective (Nod+Fix+) nodules on Lotus pedunculatus, a determinate nodulating host legume, but, in contrast, induced the formation of ineffective (Nod+Fix-) nodules on Leucaena leucocephala, an indeterminate nodulating host legume. Each rough, PN1 84-derived EPS mutant, c arrying its complementing cosmid, was fully effective on L. leucocephala. PN4 1 15, a streptomycin resistant derivative of the restricted, effective host range R . loti strain NZP2213, was shown to be Calcofluor-dark. PN4 1 1 5 was shown to produce an EPS, which fails to bind Calcofluor, that is acetylated to approximately the same extent as the EPS produced by PN1 84. Like PN1 1 77, PN4 1 15 was shown to produce only a small amount of high molecular weight EPS. Examination of 1 H-NMR spectra of EPS from PN4 1 1 5 and the smooth, PN1 84-derived EPS mutants suggests that these strains produce an EPS of similar structure, with the exception of the degree of 0- acetylation. Three non-mucoid, Calcofluor-bright, EPS mutants were generated by Tn5 mutagenesis of PN4 1 15. Each mutant was shown to carry a single, independent Tn5 insertion. Cosmids could not be isolated which stably complemented the mutation carried by each mutant. None of the mutants produced EPS, but all three mutants produce a Calcofluor-binding EPS, possibly cellulose. All three PN4 1 15-derived EPS mutants induced the formation of fully effective nodules on Lotus corniculatus, a determinate nodulating host legume. On L. leucocephala, PN4 1 15 induced the formation of both small, ineffective, nodular swellings and large, ineffective, tumour-like structures. Occasionally, a low level of nitrogen fixation was observed. In contrast, the PN41 15-derived EPS mutants all induced the formation of only small, ineffective, nodular swellings. These results, obtained in isogenic Rhizobium backgrounds, support suggestions that EPS is required for effective nodulation of indeterminate nodulating legumes, but is not required for effective nodulation of determinate nodulating legumes.
Keywords: Rhizobium loti; Calcofluor; Exopolysaccharide